PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN CV. ROBINSON DI KOTA GRESIK - Cintya Ayu Lestari; Ida Aju Brahma Ratih (Nirta Learning Center, 2025)
In the era of globalization characterized by intense business competition, employee performance has become a strategic factor in determining organizational success. Optimal performance is not only influenced by individual capabilities but also by work discipline, work motivation, and a supportive work environment. This study aims to analyze the effect of work discipline, work motivation, and work environment on employee performance at CV. Robinson in Gresik City. This study employs a quantitative approach using a survey method. The research population consists of all 70 employees of CV. Robinson, therefore the census sampling technique was applied. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis. The data analysis included validity tests, reliability tests, classical assumption tests, partial t-tests, simultaneous F-tests, and the coefficient of determination (R²). The results indicate that work discipline, work motivation, and work environment partially have a positive and significant effect on employee performance. Simultaneously, the three independent variables also have a significant effect on employee performance. The coefficient of determination (Adjusted R²) of 0.502 indicates that 50.2% of the variation in employee performance can be explained by work discipline, work motivation, and work environment, while the remaining percentage is influenced by other factors not examined in this study. This research contributes theoretically to the development of human resource management studies, particularly in the context of small and medium enterprises (SMEs). Practically, the findings are expected to provide managerial insights for CV. Robinson to improve employee performance through consistent work discipline, enhanced work motivation, and the creation of a conducive work environment.